(Dis)-Trust in transitioning ventilator-dependent children from hospital to homecare. (December 2015) - Manhas, Kiran Pohar; Mitchell, Ian
Background: Scholarly work is needed to develop the conceptual and theoretical understanding of trust to nursing practice. The transition from hospital care to complex pediatric homecare involves nurses in myriad roles, including management and care provision. Complex pediatric homecare transforms children, families, professionals, and communities, but its exact implications are unclear. Research objectives: To conduct an ethical inquiry into the role and responsibilities of nurses in the qualitative experience of adults involved in the hospital-to-home transition of young, ventilator-dependent children. Research design: We followed methods described by Franco Carnevale. We used a sociologically grounded theoretical orientation—trust—to re-interpret qualitative data for an ethical inquiry into a specific facet of that data. Participants and study context: The participants included 26 adults, including 14 nurses, involved in the hospital-to-home transition in a Canadian province. Participants represented family, hospital, home, and government. Ethical considerations: The Conjoint Health Research Ethics Board at the University of Calgary approved this study. Findings: First, the concept and practice of trust was salient to the experience of transition. For example, responsibilities' allocation between hospital-based professionals to mothers, home-based nurses, and non-professionals necessitated reliance and vulnerability. Second, the consequences of distrust connected to recognized challenges. For example, tensions along rural–urban, medical-family, and professional–personal divide each revealed suspicion and uncertainty that led to isolation and anxiety for all involved. Third, recommendations to improve the experience and mitigate the challenges of transition can be grounded in trust promotion. For example, transition-specific education programs and codes of ethics would promote openness, recognize mutual vulnerability, and advance trust in transition. Conclusions: The challenges to transition evidenced distrust, while trust represents a powerful tool to counter these challenges and their implications. A climate of trust could bridge divides between mothers and professionals; rural and urban professionals; and professionals with differing relationships with the family.